China's maritime boundaries in the South China Sea : historical and international law perspectives - Li, Jinming, 1944- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Maritime boundary disputes in the South China have existed for centuries and researchers from a variety of countries have analysed the situation from a great many points of view. Yet, and despite its status as one of the major countries in the region, Chinese perspectives have often been absent from the international literature. This book redresses that balance. Bringing together scholarship from History and International Law, this book provides a lens through which maritime territorial disputes in the South China Sea can be interrogated. Not only does it detail the historical and jurisprudential evidence that support maritime boundaries in the South China Sea for different stakeholders, but it also clarifies some misconceptions related to China's nine-dash lines by referring to the United Nations Convention on the Law of the Sea. Moreover, the book offers in-depth discussion and observation on the most recent developments in the South China Sea. This book is an essential resource for researchers, teachers and students who specialize in Southeast Asian Studies, China maritime studies, and the international law of the sea"--
Geographical overview of China's maritime boundaries in the South China Sea -- Chinese historical records of the South China Sea -- Shitang and Changsha within China's maritime boundaries in the South China Sea -- South China Sea in the measurements of the Four Seas of the Yuan Dynasty -- Why are Hoang Sa and Truong Sa of Vietnam not Xisha and Nansha of China : some evidence from historical sources -- China's development and administration of Xisha and Nansha Islands -- China's dotted line in the South China Sea : its background and ramifications -- Legal status of the dotted line in the South China Sea : historic waters, territory boundary line or an island ownership line? -- A critical review of research on the legal status of the dotted line in the South China Sea -- China's struggle for sovereignty over Xisha and Nansha Islands before and after the Second Sino-Japanese War -- China's dispute with the Philippines over the Nansha Islands : perspective of international law -- Sino-French border demarcation disputes and maritime boundary delimitation in the Gulf of Tonkin -- UN Convention on the Law of the Sea and the South China Sea disputes -- Latest developments in the South China Sea and China's responses -- Current situation in the South China Sea and Vietnamese policy.
OCLC-licensed vendor bibliographic record.
Keywords: Jurisdiction, Territorial -- China; Maritime boundaries -- South China Sea; Territorial waters -- South China Sea; Sovereignty; South China Sea -- International status; South China Sea -- History; China -- Boundaries -- History; Islands of the South China Sea; POLITICAL SCIENCE / International Relations / General